2014
DOI: 10.1080/19338244.2014.904265
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Relationship Between Orally Administered Ammonium Perchlorate and Urine Perchlorate Concentrations in Rats: Possible Biomarker to Quantify Environmental Ammonium Perchlorate Exposure on Thyroid Homeostasis

Abstract: To evaluate the feasibility of urine perchlorate as a biomarker of ammonium perchlorate (AP) exposure and to explore the correlation between the thyroid function indicators and the perchlorate concentrations, a sensitive and selective ultra-high-performance liquid chromatography-mass spectrometry (UHPLC-MS) method was developed to detect perchlorate in urine samples. Rats were orally administrated with different doses of perchlorate. Serum free thyroxine (FT4), free triiodothyronine (FT3), and thyroid-stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…Likewise, the accumulation of perchlorate in the milk powder and rice groups also showed a pattern of feces > urine > body, whereas the bioaccumulations in the body for these two food constituent groups were 55 and 58% lower than that in the control group, respectively. These findings are inconsistent with those from previous rat studies conducted with ammonium perchlorate aqueous solution, which have demonstrated that urinary excretion is the main pathway for elimination of perchlorate from the body. Of note, the highest bioaccumulation of perchlorate in the pork and lettuce groups was in the urine followed by the feces and body. This finding was presumably associated with the highest moisture content occurring in pork and lettuce feeds among the investigated foods.…”
Section: Results and Discussioncontrasting
confidence: 59%
“…Likewise, the accumulation of perchlorate in the milk powder and rice groups also showed a pattern of feces > urine > body, whereas the bioaccumulations in the body for these two food constituent groups were 55 and 58% lower than that in the control group, respectively. These findings are inconsistent with those from previous rat studies conducted with ammonium perchlorate aqueous solution, which have demonstrated that urinary excretion is the main pathway for elimination of perchlorate from the body. Of note, the highest bioaccumulation of perchlorate in the pork and lettuce groups was in the urine followed by the feces and body. This finding was presumably associated with the highest moisture content occurring in pork and lettuce feeds among the investigated foods.…”
Section: Results and Discussioncontrasting
confidence: 59%
“…The dose of NaClO 4 treatment was chosen based in previous studies that evaluated the deleterious effects of chronic perchlorate exposure on thyroid function . Additionally, this dose is expressively lower than the dose used in several previous studies . Male rats were used in this study to avoid the hormone fluctuation that is usually observed in female rats (estrous cycle).…”
Section: Methodsmentioning
confidence: 99%
“…Short‐term low‐level perchlorate exposure apparently does not affect thyroid function in humans . Conversely, several studies have reported significant alterations in the thyroid axis of chronically perchlorate exposed rats, humans, amphibians, and fishes . Even so, the regulation of gene and protein expression in the hypothalamus, pituitary and thyroid by chronic perchlorate exposure was not completely elucidated.…”
Section: Introductionmentioning
confidence: 98%
“…A dose-response sigmoid curve has been reported for describing NIS sensitivity to ClO 4 − inhibition in different species and the half maximal inhibiting concentration in humans was found at 1.566 μM [ 43 ]. To confirm these experimental results, an orally delivered acute exposure to up to 520 µg/kg of body weight (bw) induced a significant increase in serum thyroid stimulating hormone (TSH) levels, with a relevant decline in serum-free levothyroxine concentrations [ 44 ]. On the other hand, it is thought that a chronic low-dose exposure to ClO 4 − , normally observed as the consequence of food and drink intake, could impair thyroid function by reducing iodine uptake particularly in predisposed individuals, such as those with an underlying iodine deficiency [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%